Assessing the fodder potentials of drought-tolerant maize (Zea mays L.) hybrids in West Africa - Amole, Tunde A.; Adekeye, Adetayo; Bakare, Bazit; Meseka, S.; Mengesha, W.; Menkir, A. (Hindawi Limited, 2022)
The study evaluated the fodder potential of 42 promising drought-tolerant (DT) three-way cross maize (Zea mays L.) hybrids, 11 commercial hybrid checks, and 1 local variety check under irrigation. Agronomic and laboratory trials were conducted to determine their morphological traits and fodder potential. Hierarchical cluster analysis (HCA) to group cultivars into clusters is based on quantity, quality, and the combination of both variables. Selection of potential food-feed cultivars was based on the quantity traits (grain and biomass yield) and quality traits crude protein (CP), in vitro organic matter digestibility (IVOMD), and metabolizable energy (ME). Variation was found for dry matter yield (DMY) at harvest as commercial hybrid recording the maximum DMY of 14.1 t ha−1 and the highest grain yield of 1.4 t ha−1 (P < 0.01), while local check produced a minimum grain yield of 0.54 t ha−1 (P < 0.01) with grain moisture content range between 8.4 and 11.6%. The maximum mean ash content was 5.8% for DT hybrids. Average CP was the highest in commercial hybrids with a value of 6.1%. The mean values for ME were similar (P > 0.01) in both commercial hybrids (7.2 MJ/kg DM) and DT hybrid (7.2 MJ/kg DM), while the highest ME (7.6 MJ/kg DM) was recorded for the local check. Ranking of the hybrids based on grain yield, DMY, CP, ME, and IVOMD showed that cluster subgroup A3 (M1124–24, M1527-7, 30F32, and M1427-6) and A4 (M1427-3, SC637, and M1627-11) exhibited the best potential traits and can therefore be recommended for commercial cultivation following adoption trials by farmers.